Modeling hydrotime and threshold tolerance to salinity on germination different species Basil (Ocimum basilicum) - سدابه جهانبخش; قاسم پرمون; حمیده آزادقوجه بیگلو; ali ghatei (علوم و فناوری بذر ایران)
In order to study effect of salinity and drought stress on germination and Seedling growth and fitness model hydrotime and threshold tolerance to salinity in two different species Basil, a factorial experiment in a randomized completely design was conducted at University of Mohaghegh Ardebili in 2015. Experimental treatments included was two species of basil (Purple basil and Red basil), different salts (Manitol, NaCl+K2SO4, K2SO4 and NaCl) and different potentials (0, -3, -6 and -9). Model output result showed, germination rate in drought stress coundition on Red basil (θH= 37.32) highest than Purple Basil (θH= 37.32) and uniformity of germination in purple basil (σψb=3.37) less than Red basil (σψb=1.44). Also Red basil higher tolerance drought compared with Purple basil. Threshold tolerance to salinity in germination stage showed, in Purple Basil at NaCl, K2SO4 and NaCl+K2SO4 had threshold tolerance -0.59, -0.13 and -0.87 bar and in Red Basil equle -0.31, -0.25 and -2.88 . Salinity and drought stress were causing reduced in the seedling growth and seed vigor index. The most (0.92) and least (0.78) on the use of the reserves in the case of purple basil of NaCl and NaCl + K2SO4, respectively, was observed at the same time. This is while that, the highest use of the reserves on the red basil K2SO4 salt and least amount was obtained application of NaCl. The highest vigor weight index of purple basil was observed of zero osmotic potential. The least weight index purple basil was obtained of the potential -9 bar Mannitol.